Representations of female sexuality in fairy tale illustrations and text, with specific reference to the Brothers Grimm's The handless maiden - Meyer, Berry (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Visual Arts))--University of Stellenbosch, 2010.